BJS-04 OUTCOMES OF OPEN VERSUS ROBOTIC-ASSISTED LAPAROSCOPIC POSTERIOR COMPONENT SEPARATION IN COMPLEX ABDOMINAL WALL REPAIR. A RETROSPECTIVE MULTICENTER CASE-CONTROL STUDY. (13th October 2022) - Dewulf, M; Hiekkaranta, J; Mäkaräinen, E; Saarnio, J; Vierstraete, M; Ohtonen, P; Muysoms, F; Rautio, T
Abstract: Background: Transversus abdominis release (TAR) is a relatively new surgical technique in the treatment of complex ventral hernias. The aim of this study is to compare outcomes of open (oTAR) versus robotic-assisted (rTAR) posterior component separation by TAR. Methods: Consecutive patients at two European hernia centers who underwent bilateral TAR were included. A retrospective analysis of a prospectively maintained database and the electronic medical record was performed. Primary endpoint of the study was length of postoperative hospital stay. Results: Data from 90 rTAR and 79 oTAR operations was evaluated. Patient demographics were similar between groups in terms of age, sex, body mass index and comorbidities. There were more smokers and hernias were larger in the oTAR group (width 8.7 cm vs 10.0 cm; p=0.031, length 11.6 cm vs 14.1 cm; p=0.005). Length of postoperative hospital stay was significantly shorter in the rTAR group (3.4 days vs 6.9 days; p<0.001). There were significantly more overall and serious short-term complications (Clavien-Dindo ≥ grade III) in the oTAR group (7.8% vs 20.3%; p=0.018), and surgical site infections were more common in the oTAR group (3.3% vs 12.7%; p=0.010). During a median follow-up time of 19 months in the rTAR group and 43 months in the oTAR group, reoperation rates (4.4% vs 8.9%; p=0.245) and recurrence rates (5.6% vs 5.1%; p>0.9) were similar. Conclusion: Patients with ventral incisional hernias who undergo bilateral rTAR have a significantly shorter length of postoperative hospital stay and significantly less short-term complications when compared to patients undergoing bilateral oTAR.